PERTUMBUHAN LAMUN HASIL TRANSPLANTASI Enhalus Acorides DI PADANG LAMUN TELUK AMAHAI - Calvin Talakua; Yuliana Rumengan (Jurnal Biosilampari : Jurnal Biologi, 2020)
The condition of seagrass beds in Amahai Bay is relatively fertile, with a fairly high and wide density. Enhalus acoroides was chosen as a type of seagrass used for transplants in this study because Enhalus acoroides was quite abundant in the waters of Amahai Bay. Seed availability is one of the factors that need to be considered in the transplant business. There are several points in the waters of Amahai Bay where seagrass conditions do not grow evenly. Many fishermen who do fishing activities in the seagrass area inadvertently damage the ecosystem in the seagrass beds in that location. Under these conditions, it is important to do seagrass transplants so that the seagrass ecosystem is not increasingly damaged due to many human activities or natural factors. This experimental field research was carried out comparing the growth of transplanted seagrass Enhalus acoroides using the anchored sprig method. Determination of the location of the study carried out by the method of purposive random sampling. The research station in the waters of the village of Amahai at the substrate location of the muddy sand bottom with a depth of 0.85-1.5m. The station is divided into 3 observation points, with each location given 3 plots of 1x1m size with a transplant of 16 stands in each plot. The highest leaf growth rate for transplanted seagrass is at station 2, which is 3.76 mm.hr-1 on young leaves and 1.86 mm.day-1 for old leaves. And there is a difference in the speed of growth between the growth of natural seagrass and transplanted seagrass. The difference in transplantation stations has a very significant effect on the growth of seagrass leaves.